Influence of access to HIV/AIDS information on the knowledge of federal university undergraduates in Nigeria (2018)
Information and knowledge are the foremost tools in fighting the scourge of HIV/AIDS. Previous studies have focused more on HIV/AIDS and Nigerian undergraduates’ attitudes, beliefs and protective practices than how information factors influence their knowledge of the pandemic. This study, therefore, investigated the influence of access to HIV/AIDS information on its knowledge among undergraduates of federal universities in Nigeria. The study adopted the descriptive survey research design, with a combination of the purposive, proportionate and stratified random sampling technique used to select 1,679 undergraduates from five universities across five geopolitical zones of Nigeria. Questionnaire was the instrument used for collecting data, which were analyzed using Pearson’s product moment correlation and multiple regression. The most accessible sources of HIV/AIDS information among undergraduates were television (94.5 %), radio (93.0 %) and the Internet/ICT centers (90.5 %). The types of HIV/AIDS information frequently assessed were information on how to refuse sex (Mean = 3.15), how to be faithful to one partner (Mean = 3.12), sharing of sharp objects (Mean = 3.12), blood transfusion (Mean = 3.11), unprotected sexual intercourse (Mean = 3.10) and how to use condoms correctly (Mean = 3.09). Access to HIV/AIDS information (r = 0.15) resulted in positive significant relationships with HIV/AIDS knowledge, thus access to HIV/AIDS information has a positive influence on the promotion of knowledge of HIV/AIDS among undergraduates. The level of study was also a predictor of HIV/AIDS knowledge, which was not the case for factors of age, discipline, gender, marital status, tribe and religion. The AIDS service organizations and program developers should come up with strategies that would strengthen and improve the content, accuracy and ease of understanding of HIV/AIDS information that students have access to in order to facilitate its use.